IMPLEMENTASI ALGORITMA APRIORI DAN FP-GROWTH UNTUK PENEMPATAN BUKU PADA PERPUSTAKAAN (STUDI KASUS : UBSI – BOGOR) - Nurlaela, Dini; Utami, Lila Dini; Widiastuti, Lisda (Jusikom : Jurnal Sistem Komputer Musirawas, 2023)
The library is a storage place for a diverse collection of knowledge books, magazines, and other media that is organized specifically for easy use by users. In arranging the placement of books in the library, the books are grouped according to categories and given specific numbering. Although the grouping of books has been done based on categories, the placement of books has not taken into account the popularity level of books that are frequently borrowed. As a solution to address this issue, the researcher will use data mining methods, specifically the fp-growth algorithm, especially the apriori method, to determine patterns for arranging the layout of books in the library. This system is expected to help simplify the process of determining book arrangements that better suit the needs of users. The implementation results using RapidMiner show that the highest combination pattern of library book layouts is for the book titled Aplikasi Komputer Akuntansi Menggunakan ABSS Premier Versi 20 and Metode Penelitian with a support level of 60% and a confidence level of 100%.